Factores que influyen en la rentabilidad de las pequeñas y medianas empresas del sector gastronómico - Rodríguez Quezada, Estela (2024)
The food sector has been one of the most affected economic areas due to the restrictions that were put in place to mitigate the spread of Covid-19 during the pandemic. The purpose of this body of research was to determine the factors that affected the profitability of Chilean small and medium-sized companies in the food sector, from a contingency perspective and from the standpoint of resources and capability. To do this, quantitative research was conducted with a sample of 59 companies. The results of the logistic regression analysis indicated that when firms made three or fewer workers redundant, the probability that their performance would improve or remain the same rose by 422%. On the other hand, for each additional decision the firm made, this likelihood fell by 51%. Technology and size were not relevant for these types of companies.